2010
DOI: 10.1016/j.pupt.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macrolides on antigen-induced increases in cough reflex sensitivity in guinea pigs

Abstract: Hence, they are used for both acute and chronic inflammatory airway diseases.However, the effects of these agents on allergic airway disorders presenting with an isolated chronic cough, such as non-asthmatic eosinophilic bronchitis and eosinophilic tracheobronchitis with cough hypersensitivity (atopic cough), still remain to be elucidated.Objective: To determine if macrolides are effective in the management of chronic cough caused by eosinophilic airway inflammation. Methods:The cough reflex sensitivity to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several findings have suggested that the capsaicin-induced cough is mediated mainly by the activation of the transient receptor potential vanilloid type channel-1 (TRPV1), a capsaicin receptor on the terminal of the nonmyelinated C-fibers and thin myelinated Ad-fibers [30]. Several studies have also reported that immunosensitization may facilitate the release of tachykinins from C-fiber endings by the stimulation of capsaicin.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings have suggested that the capsaicin-induced cough is mediated mainly by the activation of the transient receptor potential vanilloid type channel-1 (TRPV1), a capsaicin receptor on the terminal of the nonmyelinated C-fibers and thin myelinated Ad-fibers [30]. Several studies have also reported that immunosensitization may facilitate the release of tachykinins from C-fiber endings by the stimulation of capsaicin.…”
Section: Discussionmentioning
confidence: 99%